Researches of “Teaching and Learning on ESD” Over the Last Two Decades: Bibliometric Analysis - Wardani, Duhita Savira; Widodo, Ari; Syaodih, Ernawulan; Muslim, Muslim (KnE Social Sciences, 2025)
This study aims to provide an overview of ‘teaching and learning on ESD’ research in terms of scientific production, preferred publication venues, most involved researchers and countries (including collaborations). Data collection was done by extracting articles from Scopus online database system. The output was exported in BibTex format and was converted to a data frame through a function in bibliometrix. The main findings point to a continuous increase in research output in the field ‘teaching and learning on ESD’ over the last two decades. Furthermore, they indicate a shift regarding the research foci. While formerly mainly papers on the ESD were published, recently, an increase in the relevancy of empirical studies on the ‘teaching and learning on ESD’ can be observed. However, this study only focused on articles published in scientific journals so that future studies can also consider other sources books or conference proceedings.